Urgensi Pendidikan dalam Budaya Politik - Luthfiyah Luthfiyah (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2015)
The crisis of nation is caused by the crisis of inner self and moral degradations, that politic which must be oriented to safety people, but show emphasizing to individual or group orientation finally the politic, which must have service character precisely dominated and patronage character. So, it is significant to develop cognition, affection, and psicomotoric componens on a simultant scale through education. However education has antisipatoris and preparatoris characters. The identification of democaration values and provide a model through civic education will be concrete the fundamental function of education in effort to create the humanis people and shaped unresistant education to reality. So, education can cange political culture.